2005
DOI: 10.1111/j.1526-4610.2005.05189.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cluster Headache Attacks With Less Than 6 mg Subcutaneous Sumatriptan

Abstract: We conclude that sumatriptan in doses less than 6 mg can be effective in the acute treatment of cluster headache attacks. We suggest that patients should have experience in their individual efficacy of sumatriptan doses less than 6 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…One such trial reported an efficacy for oxygen of 66.7% against 98.0% for 6 mg injectable sumatriptan (after 15 minutes), though this study population was not medication‐naïve and included a high number of known sumatriptan responders and fewer known oxygen responders . Furthermore, the oxygen flow rates (at least 7 L/min) and masks (not specified) could not be verified to be optimized . Presently, injectable sumatriptan would appear to be the most appropriate comparator to oxygen; in the current survey analysis, both therapies were effective when oxygen was inhaled at sufficiently high rates.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…One such trial reported an efficacy for oxygen of 66.7% against 98.0% for 6 mg injectable sumatriptan (after 15 minutes), though this study population was not medication‐naïve and included a high number of known sumatriptan responders and fewer known oxygen responders . Furthermore, the oxygen flow rates (at least 7 L/min) and masks (not specified) could not be verified to be optimized . Presently, injectable sumatriptan would appear to be the most appropriate comparator to oxygen; in the current survey analysis, both therapies were effective when oxygen was inhaled at sufficiently high rates.…”
Section: Discussionmentioning
confidence: 79%
“…Despite being a mainstay treatment for cluster headache, oxygen is still considered investigational by the Centers for Medicare & Medicaid Services, thus hindering its usage in this disabling condition. There are several prospective studies investigating oxygen in cluster headache . One such trial reported an efficacy for oxygen of 66.7% against 98.0% for 6 mg injectable sumatriptan (after 15 minutes), though this study population was not medication‐naïve and included a high number of known sumatriptan responders and fewer known oxygen responders .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sumatriptan s.c. (6 mg) has been shown to be effective both on pain and associated symptoms [248250]. When administered for long periods, it maintains its efficacy without tachyphylaxis and with a good safety profile [251, 252].…”
Section: Cluster Headache (Ch)mentioning
confidence: 99%
“…L'effet est souvent plus rapide, permettant de contrôler la crise en 5 à 10 minutes (AP). Des doses de moins de 6 mg (3 mg et 2 mg) peuvent éga-lement être efficaces (grade C) [63]. En l'absence de contre-indications (pathologies cardio-et neurovasculaires, l'hypertension artérielle non contrôlée, allergie aux sulfamides), le sumatriptan est un traitement de première intention de la crise d'AVF.…”
Section: Triptansunclassified